Challenges in accessing the insertion of the intrauterine device in primary health care (Research, Society and Development, 2023)
Objective: To understand how access to intrauterine device offers occurs for women at the Primary Health Care level. Methodology: This is an integrative literature review. Databases were used, Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, UFSC University Library and Virtual Health Library, combining the descriptors: Primary health care; Intrauterine Device and Primary Care Nursing. As inclusion criteria, articles published between 2012 and 2022, in Portuguese and English, were used. Exclusion criteria were articles outside the analysis period, studies unavailable in full, duplicates of articles and articles that do not portray the proposed theme. Results:10 articles were found that correspond to the theme, and it is possible to list four categories of analysis: The IUD approach in health policies; Difficulty in accessing the IUD; IUD and women's age group and IUD offer and counseling in Primary Health Care. Conclusion: This study allowed us to identify the barriers that contribute to the low use of the intrauterine device among users of Primary Health Care and also to assess which factors that hinder the full use and insertion of the intrauterine device.